The Role of Jam'iyyah Hadiyyu and Regular Religious Study Groups in Finding Peace of Life in the Aurod Istiqomah Assembly, Jatisawit Village, Jatibarang District, Indramayu Regency - Siti Nadya Fadlilah (Diplomasi : Jurnal Demokrasi, Pemerintahan dan Pemberdayaan Masyarakat, 2025)
Peace of mind is an essential human need often sought through spiritual approaches, especially in modern society, which is filled with pressure and complexity. This study aims to explore the role of Jam’iyyah Hadiyyu and regular religious studies in helping congregants find peace of mind in the Aurod Istiqomah Assembly, Jatisawit Village, Jatibarang District, Indramayu Regency. The study used a qualitative approach with a case study method, involving three key informants selected purposively. Data collection techniques included in-depth interviews, participant observation, and documentation, with data validation through triangulation. The results showed that structured and consistent religious activities, such as congregational dhikr, aurod recitation, and religious studies, significantly contributed to increasing inner peace, spiritual resilience, and social support among congregants. Participation in Jam’iyyah Hadiyyu not only strengthens the spiritual dimension but also forms a supportive social network, thus becoming a safe space in facing life’s challenges. Therefore, it can be concluded that Jam'iyyah Hadiyyu and regular religious study groups have transformative value in improving the spiritual and social quality of life of the congregation.